Association of Various Factors in Terms of Pathological Response in Breast Cancer Patients Receiving Neoadjuvant Chemotherapy - Zargham, Anum; Ahmad, Riaz; Bangash, Mussavir Hussain; Tufail, Umair; ., Ibtisam; Babar, Anil (Pakistan Armed Forces Medical Journal, 2023)
Objective: To analyze the association of various factors in terms of pathological response among breast cancer patients. Study Design: Cross-sectional study. Place and Duration of Study: Oncology Department, Combined Military Hospital, Rawalpindi Pakistan, from Jan 2019 to Jun 2020. Methodology: This study was conducted on 82 female patients with advanced breast cancer who required neo-adjuvant chemotherapy followed by surgical tumour resection. The pathological response was classed as complete, partial, and no response based on histological findings on resected tumour sample. In addition, the age of the patient, stage of disease at presentation, intrinsic (molecular) subtypes and pathological subtype were the factors correlated with response to treatment in the target population. Results: A total of 82 female patients were included in the final analysis. The mean age of the patients was 47.421±8.857 years. 27(32.9%) had a complete pathological response, 34(41.5%) had partial, and 21(25.6%) had no response to the neoadjuvant therapy. Intrinsic subtypes of the tumour were statistically significantly associated with pathological response to neoadjuvant therapy (p-value<0.05) in our study participants. Conclusion: Considerable number of patients with advanced breast cancer showed pathological responses to neoadjuvant chemotherapy. In addition, intrinsic subtyping significantly predicted pathological response to therapy in our patients, with triple-negative patients having more chances of complete response to neoadjuvant chemotherapy.